Characteristics of Aeromonas hydrophila isolated from tilapia (Oreochromis niloticus) - Arwin, M.; Ijong, Frans G.; Tumbol, Reiny (AQUATIC SCIENCE & MANAGEMENT, 2016)
Title (Bahasa Indonesia): Karakteristik Aeromonas hydrophila yang di isolasi dari ikan nila (Oreochromis niloticus) Information related to bacteria Aeromonas hydrophila that infects almost all freshwater fish and brackish water fish with low salinity that causes significant losses to fish farmers is highly needed. Thus this study aimed to characterize some isolates of A. hydrophila from several farms. The method used in this research was the exploratory-description method. The isolates used in this study were from Denpasar, Luwuk and Manado. The isolates were then identified using a series of microbiological test which included test motility, gram test, haemolysis test and a series of biochemical tests. The results showed that haemolysis test of isolates of A. hydrophila in hemolysis from Manado was α type weheras Denpasar and Luwuk were β-type. Catalase test and oxidase test were positive all isolates. TSI test showed Acid-Alkaline for Manado and Luwuk isolates but Acid-acid for Denpasar isolates. Indol and MR test twere positive for Manado and Denpasar isolates, whereas Luwuk was negative. Vp, Citrate and Urea tests were negative for all siolates and OF test was fermentative. Gelatinase and DNase test were positive for all isolates. Test NaCl 4% for isolates Manado and Denpasar Positive, negative Luwuk. 6% NaCl third test negative isolates. The incubation temperature at 37% was positive for Manado isolates, Denpasar and Luwuk were negative.The motility test was positive for Manado and Denpasar isolates, whereas Luwuk isolate was negative. The gas glucose test was negative for Manado isolates, Denpasar and Luwuk isolates were positive. Sugars test on Glucose was positive for all isolates, lactose-negative, Sucrose was negative Manado but positive for Denpasar Luwuk; whereas in Inositol and Raffinosa tests, all isolates were negative and KCN test was positive for all. From the results of this study it can be concluded that A. hydrophila isolated from some areas have slightly different characteristics from one another. Informasi yang berhubungan dengan bakteri Aeromonas hydrophila yang menyerang hampir semua ikan air tawar dan ikan yang dipelihara di tambak dengan salinitas rendah dan menyebabkan kerugian yang cukup berarti bagi pembudidaya ikan sangat dibutuhkan. Untuk itu tujuan dari penelitian ini adalah untuk mengikarakterisasi beberapa isolat A. hydrophila yang berasal dari beberapa lokasi budidaya. Metode yang digunakan dalam penelitian ini adalah metoda eksploratif-deskripsi. Isolat yang digunakan berasal dari Denpasar, Luwuk dan Manado. Isolat yang ada selanjutnya diidentifikasi dengan menggunakan serangkian test mikrobiologi yang meliputi test motilitas, uji gram, uji hemolisis dan serangkaian uji biokimia. Hasil menunjukkan bahwa isolat A. hydrophila pada uji hemolisis bertipe α (Manado), bertipe β (Denpasar, Luwuk), Uji Katalase dan oksidase ketiga isolat positif, Uji TSIA untuk Manado dan Luwuk Asam-Alkali tetapi untuk Denpasar Asam-Asam. Uji Indol dan MR Untuk Manado dan Denpasar Positif sedangkan Luwuk negatif. Uji Vp, Citrat dan Urea Ketiga isolat negatif; dan Uji OF ketiganya Fermentatif. Uji Gelatinase dan DNase ketiganya positif. Uji NaCl 4% untuk isolat Manado dan Denpasar Positif, Luwuk negatif. Uji NaCl 6% ketiga isolat negatif. Suhu inkubasi pada 37% Manado positif, Denpasar dan Luwuk negatif. Untuk Uji Motilitas, isolat Manado dan Denpasar positif, sedangkan isolat Luwuk negatif. Uji Gas glukosa, isolat Manado negatif, isolat Denpasar dan Luwuk positif. Uji gula-gula pada Glukosa ketiganya positif, laktosa Negatif, pada Sukrosa Manado negatif Denpasar dan Luwuk positif, sedangkan pada Inositol dan Raffinosa ketiganya negatif dan Uji KCN ketiganya positif. Dari hasil penelitian ini disimpulkan bawah Isolat A. hydrophila yang diisolasi dari beberapa lokasi ini memiliki karakteristik yang sedikit berbeda satu dengan yang lainnya.